THE CORRELATION BETWEEN ENVIRONMENTAL HEALTH KNOWLEDGE AND HEALTH BEHAVIOUR TO HEALTH PROTOCOL COMPLIANCE IN LIMITED TEACHING LEARNING PROCESS AT SCHOOL - Yuliani Taufik; Rita Retnowati; Yossa Istiadi (Universitas Pakuan, 2022)
This study aims to see: (1) the correlation between environmental health knowledge and the implementation of health protocols in compliance in limited teaching learning process at school; (2) the correlation between health behavior and the implementation of health protocols compliance in limited teaching learning process at school; and (3) the correlation between environmental health knowledge and health behavior on theimplementation of health protocols in compliance in limited teaching learning process at school. This research is a correlational quantitative research with sampling using a simple random sampling technique. The questionnaires were distributed to students of XI level in senior high school in Sub-Rayon Cigombong, Bogor with a population of 879 people and a research sample of 503 people. Data was collected using a questionnaire that had been tested for validity and reliability. Analysis of research data using standard error normality test, variance homogeneity test, regression linearity test, and hypothesis testing. The results of the study stated that there was a very significant positive relationship between knowledge about environmental health and the implementation of health protocols in compliance in limited teaching learning process at school with a contribution of 15.1%. There is a very significant positive relationship between health behavior and implementation of health protocols in compliance in limited teaching learning process at school with a contribution of 48.3%. Knowledge of a very significant relationship, including the application of health protocols in compliance in limited teaching learning process at school with a contribution of 50.6% and fulfilling the regression equation 12 = 33.113 + 0.853X1 + 0.706X2.